2016
DOI: 10.1111/jce.12981
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Treatment and Atrial Fibrillation: A Need for Definitive Evidence

Abstract: Prevalence rates of atrial fibrillation (AF) and obstructive sleep apnea (OSA) are rising on a global scale. Epidemiological data have consistently demonstrated an independent association between the 2 conditions. Investigators pose that pathophysiologic features of OSA enable progression of the AF substrate; these features include abnormalities of gas exchange, autonomic remodeling, atrial stretch, and inflammation. Furthermore, many of the mechanistic perturbations that impact the AF substrate in OSA can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 117 publications
(198 reference statements)
0
16
0
Order By: Relevance
“…32 Continuous positive airways pressure in patients with OSA and AF reduces AF burden and improves the efficacy of AAD and catheter ablation used as part of a rhythm control strategy; however, these data are derived from observational studies only and randomised controlled trials are planned (ANZCTR register: ACTRN12616000903482). 33 Guidelines recommend that sleep studies are conducted in those patients in whom sleep apnoea is suspected and if diagnosed treatment initiated and optimised. 3,4 AF rarely occurs in the absence of any concomitant cardiovascular risk factors, historically described as 'lone AF'.…”
Section: Lifestyle Management and Modifying Risk Factors To Maintain mentioning
confidence: 99%
“…32 Continuous positive airways pressure in patients with OSA and AF reduces AF burden and improves the efficacy of AAD and catheter ablation used as part of a rhythm control strategy; however, these data are derived from observational studies only and randomised controlled trials are planned (ANZCTR register: ACTRN12616000903482). 33 Guidelines recommend that sleep studies are conducted in those patients in whom sleep apnoea is suspected and if diagnosed treatment initiated and optimised. 3,4 AF rarely occurs in the absence of any concomitant cardiovascular risk factors, historically described as 'lone AF'.…”
Section: Lifestyle Management and Modifying Risk Factors To Maintain mentioning
confidence: 99%
“…However, the efficacy of catheter ablation for AF is similar between patients without OSA and patients with OSA treated with continuous positive airway pressure treatment . Thus, detection of OSA and appropriate treatment is a prime target for intervention to improve AF treatment outcomes …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Thus, detection of OSA and appropriate treatment is a prime target for intervention to improve AF treatment outcomes. 11 Recent studies have demonstrated a reduction in nocturnal respiratory events (apnoeas and hypopnoeas) with successful direct current cardioversion (DCCV) and AF ablation procedures at short-term follow-up. 12,13 The long-term effects of randomized AF intervention on sleep data were evaluated at baseline and at 6 months utilizing the Watch-PAT200 (WP) (Itamar Medical Lts., Caesarea, Israel).…”
mentioning
confidence: 99%
“…The authors reported that despite the evidence demonstrating an association between OSA and AF, the under diagnosis of OSA in patients with cardiovascular issues such as AF, continues to be an issue (Khan et al, 2019). Nalliah, Sanders, and Kalman (2016), explained that epidemiologic studies verified an independent association between AF and OSA, and argued that the pathophysiologic process of OSA facilitates the progression of AF. The authors pointed at differences in prevalence according to the patient's sex, and suggested that OSA seems to affect males at a higher rate than females.…”
Section: Introductionmentioning
confidence: 99%
“…The authors pointed at differences in prevalence according to the patient's sex, and suggested that OSA seems to affect males at a higher rate than females. Nalliah, Sanders, and Kalman (2016), continued by saying that the prevalence rates of AF and OSA are increasing globally, with a prevalence in men and women of 17-31%, and 6.9-9% respectively. Abumuamar, Dorian, Newman, and Shapiro (2018), conducted a cohort study and assessed patients who were referred to a cardiac clinic.…”
Section: Introductionmentioning
confidence: 99%